Factors related to dosing frequency and route of administration in methotrexate intolerance among patients with rheumatoid arthritis: a cross-sectional study - Haya M. Almalag; Jawza F. Alsabhan; Abdurhman S. Alarfaj; Eman Alfi; Shorouq Albalawi; Asma A. Al-Shadaawi; Sahar A. Alshehri; Ghadah Asaad Assiri; Ibrahim Almaghlouth; Mohammed A. Omair (Therapeutic Advances in Drug Safety)
Background: Methotrexate is central to the management of rheumatoid arthritis (RA). However, its use is often limited by methotrexate intolerance. Objectives: This study aims to explore the association between alternative methotrexate dosing methods and methotrexate intolerance. Design: A cross-sectional study. Methods: A cross-sectional survey was conducted on patients with RA receiving methotrexate for at least 3 months at the outpatient clinic of King Saud University Medical City, Riyadh, Saudi Arabia. The electronic survey collected data on demographics, marital and educational status, methotrexate use, Methotrexate Intolerance Severity Score (MISS), and Health Assessment Questionnaire. Statistical analyses (univariate and linear or logistic regression) were conducted to evaluate the associations between the administration methods and methotrexate intolerance (MISS ⩾6). Results: The study included 154 patients, predominantly female (89%; mean age (standard deviation, ±SD): 50 (±12) years). Methotrexate tolerance was observed in 64% of the participants, while 36% had a MISS above the cutoff point of 6, indicating intolerance. Methotrexate-intolerant patients were younger (mean age (±SD): 47 (±12) years) than tolerant patients (mean age (±SD): 54 (±12) years; p  = 0.005). No significant differences were found between methotrexate-tolerant and methotrexate-intolerant patients regarding dose, frequency, relation to meals, and time of day. Conclusion: Methotrexate tolerance was not associated with different administration methods: split-dose versus single weekly dose, or subcutaneous versus oral administration.